2021
DOI: 10.1007/s00251-021-01226-5
|View full text |Cite
|
Sign up to set email alerts
|

Black fungus immunosuppressive epidemic with Covid-19 associated mucormycosis (zygomycosis): a clinical and diagnostic perspective from India

Abstract: The catastrophic phase of Covid-19 turns the table over with the spread of its disastrous transmission network throughout the world. Covid-19 associated with mucormycosis fungal infection accompanied by opportunistic comorbidities have emerged the myriad of complications and manifestations. We searched the electronic databases of Google Scholar, PubMed, Springer, and Elsevier until June 05, 2021, using keywords. We retrieved the details of confirmed and suspected mucormycosis patients associated with Covid-19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This correlation suggests that C. parapsilosis clones might have colonized the hospital surfaces, which increases the risk of recirculating among patients along the time and, in parallel, increases the risk of invasive infections among the most fragile ones. Previous studies, in fact, have shown, not only an increase incidence of C. parapsilosis infections in COVID-19 patients [34], but also other fungal diseases, such as Covid Associated Pulmonary Aspergillosis (CAPA) [35][36][37], mucormycosis [38][39][40] and Candida infections [41,42] (see reviews in [43,44]).…”
Section: Resultsmentioning
confidence: 99%
“…This correlation suggests that C. parapsilosis clones might have colonized the hospital surfaces, which increases the risk of recirculating among patients along the time and, in parallel, increases the risk of invasive infections among the most fragile ones. Previous studies, in fact, have shown, not only an increase incidence of C. parapsilosis infections in COVID-19 patients [34], but also other fungal diseases, such as Covid Associated Pulmonary Aspergillosis (CAPA) [35][36][37], mucormycosis [38][39][40] and Candida infections [41,42] (see reviews in [43,44]).…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to the airborne spores of fungi that enter the body through inhalation or through open wounds. Healthy people generally clear these spores from their bodies, but immunocompromised individuals or patients associated with comorbidities are the prime targets for nosocomial infections (Singh et al 2022 ). Some studies also mention that (Quinn and Bell 2022 ) people who have recovered from the infection are likely to have negative impacts on their quality of life, reduction in functional abilities, and a shortened life expectancy.…”
Section: Socio-economic Environmental and Health Implications Of The ...mentioning
confidence: 99%
“…The death rate reported was 23.5%, and the rate of recovery was reported to be 2.9%. Patients suffering from diabetes mellitus are more common in India than in other nations, and the widespread consumption of steroids along with the presence of COVID-19 creates a suitable environment for mucormycosis fungus infection to thrive [35].…”
Section: Mucormycosismentioning
confidence: 99%